Direct Iterative Protein Profiling (DIPP) - an Innovative Method for Large-scale Protein Detection Applied to Budding Yeast Mitosis - Lavigne, Régis (The American Society for Biochemistry and Molecular Biology, 2012)
The budding yeast Saccharomyces cerevisiae is a major model organism for important biological processes such as mitotic growth and meiotic development, it can be a human pathogen, and it is widely used in the food-, and biotechnology industries. Consequently, the genomes of numerous strains have been sequenced and a very large amount of RNA profiling data is available. Moreover, it has recently become possible to quantitatively analyze the entire yeast proteome; however, efficient and cost-effective high-throughput protein profiling remains a challenge. We report here a new approach to direct and label-free large-scale yeast protein identification using a tandem buffer system for protein extraction, two-step protein prefractionation and enzymatic digestion, and detection of peptides by iterative mass spectrometry. Our profiling study of diploid cells undergoing rapid mitotic growth identified 86% of the known proteins and its output was found to be widely concordant with genome-wide mRNA concentrations and DNA variations between yeast strains. This paves the way for comprehensive and straightforward yeast proteome profiling across a wide variety of experimental conditions.